2013
DOI: 10.1038/nature12757
|View full text |Cite
|
Sign up to set email alerts
|

Strong neutrino cooling by cycles of electron capture and β− decay in neutron star crusts

Abstract: The temperature in the crust of an accreting neutron star, which comprises its outermost kilometre, is set by heating from nuclear reactions at large densities, neutrino cooling and heat transport from the interior. The heated crust has been thought to affect observable phenomena at shallower depths, such as thermonuclear bursts in the accreted envelope. Here we report that cycles of electron capture and its inverse, β(-) decay, involving neutron-rich nuclei at a typical depth of about 150 metres, cool the out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
204
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(209 citation statements)
references
References 37 publications
(110 reference statements)
4
204
1
Order By: Relevance
“…The presence of Urca cooling, neutrino cooling via e − -capture/β − -decay cycles between a pair of neutron-rich nuclides in an electron-degenerate environment (Gamow & Schoenberg 1941;Tsuruta & Cameron 1970), was recently identified in the crusts of accreting neutron stars (Schatz et al 2014) and in the shallower ocean (Deibel et al 2016b). Urca neutrino luminosities depend on the energy cost for e − -capture, i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of Urca cooling, neutrino cooling via e − -capture/β − -decay cycles between a pair of neutron-rich nuclides in an electron-degenerate environment (Gamow & Schoenberg 1941;Tsuruta & Cameron 1970), was recently identified in the crusts of accreting neutron stars (Schatz et al 2014) and in the shallower ocean (Deibel et al 2016b). Urca neutrino luminosities depend on the energy cost for e − -capture, i.e.…”
mentioning
confidence: 99%
“…The finitetemperature environment enables e − -capture to proceed when |Q EC | − k B T E F |Q EC | + k B T , where k B is the Boltzmann constant, and provides phase-space for the product of the e − -capture reaction, i.e. daughter, to undergo β − -decay within the same depth-window (Schatz et al 2014). For cases in which the β − -decay rate of the e − -capture daughter is significant with respect to its e − -capture rate, a condition which is fulfilled for all odd-A nuclides due to the monotonic increase of |Q EC (A)| for decreasing Z, an e − -capture/β − -decay cycle can create an Urca pair.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For neutron stars, the thermal energy is pretty small compared with the Fermi energy, thus the standard neutron star model uses the zero-temperature approximation, the captured electrons can not be remitted because no phase space is available. Recently, Schatz et al proposed that the Urca shell may exist in the crust of superbursting neutron stars [6], the local accretion of which are supposed to beṁ = (0.1 − 0.3)ṁ Edd [7], wherė m Edd ≃ 10 5 g cm −2 s −1 is the local Eddington accretion rate. By considering the relatively high temperature (T > 10 8 K) and possible low-lying excited states E x ≲ k B T [6], Schatz et al showed that the Urca pairs may have the potential to cool the outer crust, and make the surface layers thermally decouple from the deeper crust.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schatz et al proposed that the Urca shell may exist in the crust of superbursting neutron stars [6], the local accretion of which are supposed to beṁ = (0.1 − 0.3)ṁ Edd [7], wherė m Edd ≃ 10 5 g cm −2 s −1 is the local Eddington accretion rate. By considering the relatively high temperature (T > 10 8 K) and possible low-lying excited states E x ≲ k B T [6], Schatz et al showed that the Urca pairs may have the potential to cool the outer crust, and make the surface layers thermally decouple from the deeper crust. If this is true, it will be a great challenge to current thermonuclear bursts models [8,9].…”
Section: Introductionmentioning
confidence: 99%